2017
DOI: 10.1021/acs.biomac.7b00761
|View full text |Cite
|
Sign up to set email alerts
|

Fast Hydrolysis Polyesters with a Rigid Cyclic Diol from Camphor

Abstract: 2,2:3,3-Bis(4'-hydroxymethylethylenedioxy)-1,7,7-trimethylbicyclo[2.2.1]heptane, abbreviated as CaG, is a compound obtained by transforming a ketone group to a ketal group with camphorquinone and glycerol. The CaG diol has a complex and rigid structure and two primary hydroxyl groups. A polyester series was synthesized with the CaG diol, ethylene glycol, and dimethyl terephthalate. The polyesters exhibited adequate thermal stability up to nearly 330 °C and had a high T, which steadily increased from 78 to 129 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…The much more pronounced degradation rates under acidic conditions compared to a neutral environment were attributed to the known catalyzing effect of acid or self-catalysis by carboxyl end groups. 15 Scanning electron microscopic (SEM) analysis of the final degradation films afforded valuable information on morphological alterations. For copolyesters containing high IS content (25 and 36 mol %, Figure 11), the film samples appear to have rather rough crystallization surfaces at the end of degradation testing instead of the initial smooth surfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The much more pronounced degradation rates under acidic conditions compared to a neutral environment were attributed to the known catalyzing effect of acid or self-catalysis by carboxyl end groups. 15 Scanning electron microscopic (SEM) analysis of the final degradation films afforded valuable information on morphological alterations. For copolyesters containing high IS content (25 and 36 mol %, Figure 11), the film samples appear to have rather rough crystallization surfaces at the end of degradation testing instead of the initial smooth surfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…When incorporated into step-growth polymers, they significantly increase the glass transition temperatures and synergistically enhance the hydrolytic and/or biodegradability properties of polymers, depending on the chemical and microsequential structures of polymers. Typical examples are isohexides, 2,4:3,5-di- O -methylene- d -glucitol (Glux-diol), 2,4:3,5-di- O -methylene- d -mannitol (Manx-diol), 2,3:4,5-di- O -methylenegalactitol (Galx-diol), and 2,2:3,3-bis­(4′-hydroxymethylethylenedioxy)-1,7,7-trimethylbicyclo[2.2.1]­heptane (CaG) and their corresponding dicarboxylic acids/esters. Recently, Muñoz-Guerra et al have extensively explored the synthesis and properties of the semiaromatic copolyesters based on a few monomers of this kind (Manx-diol, Glax-diol/diacid, and Glux-diol/diacid). Their results generally proved the remarkable synergistic effect of these monomers on the thermal/mechanical properties and (bio)­degradability of well-known semiaromatic polyesters including PET, PBT, and poly­(hexamethylene terephthalate) (PHT).…”
Section: Introductionmentioning
confidence: 99%
“…Camphor can also be considered as an interesting building block for the production of novel bio-based polymers, as documented by several studies on camphor-based polymers that have recently been reported in the literature [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…23,24 To recycle complex polymer mixtures as textiles, chemical recycling is considered more practical than conventional mechanical recycling. 20,22,25 In this context, polymers with acidsensitive acetal bonds (polyacetals) are particularly attractive, [26][27][28][29] because they can be conveniently acidhydrolyzed which can enable chemical recycling even from complex textiles. 25 Polyacetals exist widely in nature, including cellulose, hemicellulose, starch, chitin, etc.…”
Section: Introductionmentioning
confidence: 99%